EWSR1‐PATZ1 gene fusion may define a new glioneuronal tumor entity. (13th July 2018) - Siegfried, Aurore; Rousseau, Audrey; Maurage, Claude‐Alain; Pericart, Sarah; Nicaise, Yvan; Escudie, Fréderic; Grand, David; Delrieu, Alix; Gomez‐Brouchet, Anne; Le Guellec, Sophie; Franchet, Camille; Boetto, Sergio; et al.
Abstract: We investigated the challenging diagnostic case of a ventricular cystic glioneuronal tumor with papillary features, by RNA sequencing using the Illumina TruSight RNA Fusion panel. We did not retrieve the SLC44A1‐PRKCA fusion gene specific for papillary glioneuronal tumor, but an EWSR1‐PATZ1 fusion transcript. RT‐PCR followed by Sanger sequencing confirmed the EWSR1‐PATZ1 fusion. It matched with canonic EWSR1 fusion oncogene, juxtaposing the entire N‐terminal transcriptional activation domain of EWSR1 gene and the C‐terminal DNA binding domain of a transcription factor gene, PATZ1 . PATZ1 protein belongs to the BTB‐ZF (broad‐complex, tramtrack and bric‐à‐brac ‐zinc finger) family. It directly regulates Pou5f1 and Nanog and is essential to maintaining stemness by inhibiting neural differentiation. EWSR1‐PATZ1 fusion is a rare event in tumors: it was only reported in six round cell sarcomas and in three gliomas of three exclusively molecular studies. The first reported glioma was a BRAF V600E negative ganglioglioma, the second a BRAF V600E negative glioneuronal tumor, not otherwise specified and the third, very recently reported, a high grade glioma, not otherwise specified. In our study, forty BRAF V600E negative gangliogliomas were screened by FISH using EWSR1 break‐apart probes. We performed methylation profiling for the index case and for seven out of the ten FISH positive cases. The index case clustered apart from other pediatric low grade glioneuronal entities, and specifically from the well‐defined ganglioglioma methylation group. An additional pediatric intraventricular ganglioglioma clustered slightly more closely with ganglioglioma, but showed differences from the main ganglioglioma group and similarities with the index case. Both cases harbored copy number variations at the PATZ1 locus. EWSR1‐PATZ1 gene fusion might define a new type of glioneuronal tumors, distinct from gangliogliomas.